FACTORS AFFECTING BUSINESS PERFORMANCE THE SMALL MEDIUM ENTERPRISES OF BATIK PEKALONGAN CENTRAL JAVA, INDONESIA - Ilmiani, SE., M.Si, Sobrotul; Tubastuvi, Naelati (Majalah Neraca, 2013)
The small-medium enterprises (SMEs) of batik pekalongan having potensial contribution to the national income and to absorb labor force. Pekalongan, small city in Central Java , is one of many centers batik production in Indonesia. Eventhough recently batik becomes public fashion, to resist in the industry with the higher competition, SMEs Batik have to execute some strategy and enhance the business performance.Business performance is one of important indicators to measure the reputation and performance of SMEs that it always makes every effort to achieve an optimum business performance level. The competitive advantage is an important factor in reaching the business performance desires. One of ways to obtain a high competitive advantage is by developing functional competencies and business strategy. The purpose of this study is to analyzed the influence functional competencies including the manufacturing, marketing, innovation and business strategy, also the influence of the interaction of functional competence and business strategy on the business performance of SMEs Batik. The proxies of business performance comprises sales, sales growth, market share, market share growth, ROI (Return on Investment), ROS (Return on Sales). It is presumed that functional competence, business strategy and interaction variables has a positive effect on the business performance. The respondents are owners batik home industry in pekalongan.The result of analysis shows that production competence, marketing competence, innovative competence, interaction production competence and business strategy has a significantly positive effect on the business performance consistently. While the variable of business strategy, interaction marketing competence and business strategy, interaction innovation competence and business strategy are rejected since they are insignificant. Â Key words : SMEs batik, Â business performance, functional competency, business strategy